Oxidative stress in female dogs with mammary neoplasms - Claudia Russo; Sandra Maria Simonelli; Marcela B. Luz; Alefe C. Carrera; Isabela F. Moreno; Ana Paula F.R.L. Bracarense (Pesquisa Veterinária Brasileira, 2021)
ABSTRACT: The result of the reaction of free radicals with biomolecules is the formation of substances with the potential of inducing oxidative damage, a condition known as oxidative stress. There are voluminous literature data reporting the association, both as a cause and as a consequence, between different diseases and oxidative stress. In this study, 144 female dogs with mammary neoplasia were analyzed. The animals were submitted to clinical evaluation for disease staging, hematological evaluation, serum biochemistry (renal and hepatic function tests), and dosage of the oxidative damage biomarker, malondialdehyde (MDA), at the time of its approach and 30 days after treatment. A control group of 100 healthy animals was also submitted to determination of serum MDA levels. The mean age of the animals affected by mammary neoplasms was 9.88±2.95 (4 to 14) years, while in healthy animals it was 2.31±1.90 years (1 to 6). Of the 144 animals, 113 (78.9%) had malignant neoplasms, and 15, 21, 46, 17 and 14 animals were in clinical stage I, II, III, IV and V respectively and the carcinoma in a mixed tumor was the most frequent histological pattern in this group (26%). Thirty-one animals were diagnosed with benign neoplasms and mammary adenoma was the most frequent histological pattern in 15 animals (51.61%). Hematological changes in the preoperative period were observed in 44 (38.9%) and 12 (38.7%) animals with malignant and benign neoplasias, respectively, and there was a positive correlation between anemia and higher levels of MDA (P=0.0008) for animals with malignant tumors. Regarding serum biochemical parameters, the most frequent alterations in animals with malignant neoplasms were elevated ALT levels in 12 animals (10.6%), creatinine in 10 animals (8.84%) and urea in eight animals (7.07%). Females with benign neoplasms presented less occurrence of changes in these parameters. In the group of healthy animals (control), the mean serum MDA values were 12.08±4.18, whereas in the pre-treatment group, mean MDA was 24.80±5.74 for bitches with benign neoplasms and 32.27±10.24 for bitches with malignant tumors. A significant increase (P<0.001) in MDA levels was observed in animals with malignant mammary neoplasms when compared to healthy animals and with benign tumors. In addition, a significant reduction (P<0.001) was observed 30 days after treatment in MDA levels (27.37±7.86) in animals with malignant tumors. In conclusion, our results indicate an association between MDA seric levels and mammary neoplasms in dogs. The results suggest that this factor can be used as a biomarker of oxidative stress with a potential impact in the prognostic of mammary tumors, since significantly higher levels of MDA were detected especially in dogs carrying malignant tumors and presenting anemia.